Editorial: Tracing Actors, Actants and Relational Dynamics in Environmental Education Research - Heila Lotz Sisitka (Environmental Association of Southern Africa, 2006)
This edition of the EEASA Journal provides insight into a range of relationships in the field of environmental education, and the complexities that exist around them, as reflected in the combination of papers. This Editorial picks up on the methodological 'note' (or is it a challenge?) provided by Godwell Nhamo in his paper in this edition of the journal. He provides a description of the possibilities that actor network theory provides for describing and explaining environmental policy processes, and recommends that environmental educators consider this methodology in their analyses. In particular, he refers environmental educators to applications of actor network theory for tracing relational dynamics between actors (i.e., environmental education practitioners) and actants which are non-human referents (e.g., the UN Decade of Education for Sustainable Development and UNESCO's (2005) International Implementation Scheme). In response to his paper, I have chosen to 'pick up' on this methodological discussion in this Editorial, by considering aspects of this theoretical perspective in describing the 'happenings' that occur across the pages of this edition of the EEASA Journal. In doing so, I highlight (in part) the diversity of actors and actants that are influencing the field of environmental education, their subject matter and contexts, and I highlight the relational dynamics that become evident when one accepts a methodology that aims to trace such dynamics. In particular, this Editorial considers how 'The language of actors, actants and actor/actant-networks brings to the fore the relationships and complexities that exist around them' (Nhamo, this edition).